Methodological Framework for the Evaluation and Analysis of the Potential of the Electric Infrastructure of Ruassian Regions - Baev, Igor Aleksandrovich; Solovyeva, Irina Aleksandrovna; Dzyuba, Anatoliy Petrovich (Economy of Regions, 2017)
The article is devoted to the analysis and evaluation of the potential of the electric structure of Russian regions. The authors introduce the category of the “potential of electric infrastructure” understood as the integrated indicator characterizing the regional power infrastructure. The authors assess the potential of electric infrastructure on the basis of the proposed methodology and the developed indicators: “the ratio of electricity tariff”, “coefficient of technological connection”, “integral coefficient of electric infrastructure potential.” The article presents the results of testing the developed method on the example of the analysis and evaluation of the characteristics of electric power infrastructure of Russian regions. The result of testing was the construction of a rating of regions by the level of electric infrastructure potential. On the basis of the calculated parameters of electric infrastructure potential, we developed a map and a matrix of indicators of the potential of electric infrastructure of Russian regions. This allowed to classify Russian regions to several groups. The practical value of the map and matrix of the potential of electric infrastructure of Russian regions is the possibility to conduct the comparative assessment of the characteristics of the electric infrastructure of the territorial units and enables more informed management and decision-making concerning the choice of the most effective industrial investment. In addition, based on the developed indicators of electric infrastructure potential, the authors propose the improvement of the existing methods for the evaluation of investment potential of Russian regions. Previous research on the investment potential of regions does not take in account the characteristics of the potential of electric infrastructure. The obtained results are of a theoretical and practical importance and can be used for the energy efficiency management of territorial units as well as for the analysis ofthe potential of electric infrastructure of possible industrial investments with the aim of increasing it.